Network mobility in beyond-3G systems. - Lach, Hong-Yon (IEEE Communications magazine)
This article aims to analyze network mobility issues and requirements in the context of beyond-3G systems, and explore various approaches to the solutions, including the basic approach being pursued within the IETF NEMO working group. It starts with understanding the network mobility scenarios. Then the principle of mobile IP is revisited to serve as the basis for the subsequent discussion on the basic and advanced requirements and approaches for network mobility support. Finally, the network mobility research activities in the EU project OverDRiVE are reported.